Assistance of the MSMEs Roti Abimanyu during the pandemic to maximize profits - Angga Rizka Lidiawan; Nunung Susilaningsih; Sudjiono Sudjiono; Nabila Andriani; Risma Gesang Ayu Cahyani (Universitas Muhammadiyah Magelang, 2022)
This community service program focuses on increasing productivity at the MSMEs Roti Abimanyu during the COVID-19 pandemic with a training scheme for the use of social media and marketplaces. The target to be achieved in this activity is to increase sales, marketing, and product ordering services through the use of information technology. This activity is carried out with training and assistance in utilizing e-commerce. The result of this activity is that MSMEs Roti Abimanyu have understood marketing techniques through social media and marketplaces.